SANKSI ADMINISTRATIF KEPADA PEMBERI KERJA DALAM PENYELENGGARAAN JAMINAN SOSIAL - Sri Wahyu Handayani (Jurnal Idea Hukum, 2016)
Labor is the main capital Pancasila community development  because the purpose of manpower development is the people's welfare, therefore the rights of workers must be guaranteed.  The Government of Republic of Indonesia has a commitment to be responsible in the implementation of Social Security. It was realized its implementation by the government based on Law No. 24 of 2011 through the Social Security Agency ( BPJS ) which is a statutory body established to administer social security program. BPJS consists of Workers Social Agency and Healthcare and Social Security Agency.  Social insurance programs provided by the Government aimed at protecting the rights of Indonesian workers , but on the other hand there are employers who do not carry out its obligations.  Of course this provides a problem for workers whose position has not been balanced with employers. The government is not only responsible for the management of social security but also protection relating to administrative sanctions that may be granted to employers who neglect their obligations so that with the imposition of administrative sanctions is expected to lead to harmonious industrial relations.Keywords : administrative sanctions , employers , social security